Biomechanical analysis on drag flick at hockey indoor game - Rudiansyah, Rudiansyah; Rusdiana, Agus; Hidayat, Iwa Ikhwan; Haryono, Tono; M Syahid, Angga; Kurniawan, Tian; Salman, Salman (Departement of Sports Coaching, Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2023)
This research aims to identify the factors that influence ball speed in drag flicks in hockey. Samples were taken from amateur and professional male hockey players according to predetermined biomechanical variables. Using a type of quantitative research that focuses on observing the body mechanics of athletes from the hockey student activity unit at the Indonesian University of Education and senior athletes who have played at national and international levels. Divided into 2 group categories professional by senior athletes who have appeared in national and international events, and amateur groups by UKM HOKI UPI athletes. Each individual was allowed to carry out the movement 3 repetitions to achieve the best results, which were recorded and then analyzed via Kinovea - 0.9.5 software for each movement, then the average results for each movement phase were entered into SPSS 26 for sample testing. t test which is then compared between the influential variables obtained to find out the significant differences that exist between the processes and results of the professional and amateur groups. The results of this study show that factors that show differences in several phases that influence the results of professional teams are superior to amateur teams. Among them are total approach distance (TDA), length of pull (DL), angle of movement of the left leg knee during drag (LKA), width between two legs (SW), and stick speed (SV). The five selected independent variables show a significant correlated influence on the final speed of the ball when launched. In conclusion, this research highlights the importance of adjusting drag flick performance factors according to biomechanical variables to improve overall performance based on the results that have been analyzed in professional groups.